SUMBER DAYA MANUSIA DI INDONESIA; ANALISIS DATA SENSUS - Tadjuddin Noer Effendi (Populasi, 1992)
The aim of this paper is to analyse the quality of human resource in urban and rural areas of Indonesia. By using labor utilisation approach this study shows that although the education of labor force has increased along with the spread of educational facilities, there is a tendency that educated unemployment and underemployment are not decreased. This suggests that quite a highproportion of labor is underutilized. This reflects that technology and skill of labor are low which determine the low level of humanresource quality.